A rare case of beaten copper skull pattern associated with Treacher Collins syndrome - Sunita Gupta; Anju Garg; Khusboo Singh; Sinny Goel (Wolters Kluwer Medknow Publications, 2016)
Treacher Collins syndrome (TCS) is an autosomal dominant disorder with craniofacial abnormality. Typical features are downslanting palpebral fissures, lower eyelid colobomas, microtia, and malar and mandibular hypoplasia. Management requires a multidisciplinary team from birth through adulthood with proper planning, counselling, and surgical techniques. Here, we present a case of TCS with a very unusual and rare finding of beaten copper skull appearance on the radiograph.